STUDY OF CONCRETE FRACTURE SIMULATION USING ANSYS - AWl, AZREE AZHAR (Universiti Teknologi Petronas, 2008)
Ma,Jor problem in concrete is fracture due to excess load acting on it or failure due to tension or shear. This proJect focused on the computer simulation of concrete fracture using ANSYS software. Though. ANSYS software helps simulate the cracking and concrete fracture simulation in calculating the most important stress intensitv factor using in-built crack analvsis engine. Using several perimeters and different tvpe of load, se1eral tvpes of fracture will be getting. A concrete fracture model is analped to find the precise results in order to simulate through this project Finite-element Method is being used in this studies and Linear Elastic Fracture Model is recognized to be the most efficient fracture model to be used in ANSYS. This study of simulation will be beneficial to all in a 11 av to hm e better understanding of concrete fracture occurrence and this is important in big construction companies which use concrete as their core material construction ..